Respuesta :

Let's solve your equation step-by-step.
3

2
x
+
3
x
=
5

2
(
2
x

3
)
Step 1: Simplify both sides of the equation.
3

2
x
+
3
x
=
5

2
(
2
x

3
)
3
+

2
x
+
3
x
=
5
+
(

2
)
(
2
x
)
+
(

2
)
(

3
)
(Distribute)
3
+

2
x
+
3
x
=
5
+

4
x
+
6
(

2
x
+
3
x
)
+
(
3
)
=
(

4
x
)
+
(
5
+
6
)
(Combine Like Terms)
x
+
3
=

4
x
+
11
x
+
3
=

4
x
+
11
Step 2: Add 4x to both sides.
x
+
3
+
4
x
=

4
x
+
11
+
4
x
5
x
+
3
=
11
Step 3: Subtract 3 from both sides.
5
x
+
3

3
=
11

3
5
x
=
8
Step 4: Divide both sides by 5.
5
x
5
=
8
5
x
=
8
5

Answer:

- 5/9

Step-by-step explanation:

Step 1:

3 - 2x + 3x = 5 - 2 ( 2x - 3 )

Step 2:

3 - 5x = 5 - 4x + 3

Step 3:

3 - 5x = 8 + 4x

Step 4:

3 = 8 + 9x

Step 5:

- 5 = 9x

Answer:

- 5/9 = x

Hope This Helps :)